Cultural intelligence and global citizenship in gifted/talented students and their non-gifted peers - Ozbey, Adnan; Karduz, Fatıma Firdevs Adam (American Journal of Social Sciences and Humanities, 2023)
Cultural intelligence, or cultural quotient (CQ), and global citizenship are essential skills for individuals in today's increasingly interconnected and globalized world. Cultural intelligence helps individuals effectively navigate and understand cultural differences, promoting effective communication and cooperation. This study primarily aims to compare the cultural intelligence and global citizenship levels of gifted and non-gifted students. Another aim of the study is to discover the possible relationship level between gifted students' cultural intelligence and global citizenship levels. The relational scanning model was used, and 399 high school students attending 10th, 11th, and 12th grades were included in the study. The majority (209, or 54.1%) were non-gifted high school students and 177 (40.6%) were gifted high school students. The Cultural Intelligence Scale and Universal Citizenship Scale were employed for data collection. The results indicate that gifted students have significantly higher cultural intelligence than their average peers. Similarly, it has been demonstrated that gifted students have significantly greater global citizenship than their average peers. A significant relationship was found between gifted students' cultural intelligence levels and global citizenship levels. The cultural intelligence level of gifted students significantly predicts the level of global citizenship. Gifted students benefit from high levels of cultural intelligence and global citizenship because it enhances their capacity to engage with diverse cultures and comprehend global issues, thereby fostering their intellectual and personal development.